Canning children: abuse or educate? / Ekmil Krisnawati Erlen Joni and Salmiah Salleh (2015)
Section 31 of the child act 2001 provides the penalty for those who commit the offences of abusing, neglecting, abandoning or exposing the child and causing him or her physical or emotional injury. The penalty is a fine not exceeding RM20,000 or imprisonment for a term not exceeding 10 years or both. Nevertheless the act is silent on imposing punishment for those who involve in canning their children. Recently, the policy makers in Malaysia are currently contemplating to propose and impose severe punishment towards parents or guardian who committed such an act. This has attracted various reactions from the members of the public who support or disprove the punishment. The intention of the policy makers is to protect the children as required by the convention on the rights of the child (CRC) where Malaysia has ratified to uphold its commitment to the protection and welfare of the children. Hence, this paper will highlight the requirement in CRC and the relevant laws relate to the protection of children in Malaysia. In addition, the paper will also examine the effects on imposing punishment towards parents who involve in canning their children. It is hoped that this paper would provide a clear guideline between the rights of children and the rights of the parents to educate. While protecting the children is fundamental, nevertheless religious method of education should not be ignored. 101-113